Comparisons of Enhancers Associated Marks Prediction Using K-mer Feature - Nazeri, Sina; Lee, Nung Kion; Norwati, Mustapha (2015)
Epigenetic signatures such as chromatin and histone modification marks are prominent indicator of enhancer motif regions. While many works have been using k-mer as feature of epigenetic sequence, no comprehensive studies has been done to compare and contrast how the different choices of k-mers feature parameter affect machine learning algorithm performances. Furthermore, it is not known how effective is the k-mer feature for representing different epigenetic marksH3K4me1, DHS and p300. In this paper, a comparative study is performed to determine the accuracy, sensitivity and specificity of using k-mer feature for predicting these marks. Our results found that, classifier perform better when the k-mer length is between 4 to 6. Short k-mer length has poor accuracy, sensitivity and specificity. The k-mer feature works best for DHS sequences and has low accuracy for H3K4me1 sequences prediction. The k-mer feature is also performed poorly on specificity of DHS sequences. It can be concluded that, there are still much room for improvement of identifying better feature for representing epigenetic feature for enhancer prediction.